2021
DOI: 10.1002/cbic.202100324
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of β‐Hairpin Propensity Among Peptides with Homochiral or Heterochiral Strands

Abstract: Assemblies of racemic β‐sheet‐forming peptides have attracted attention for biomedical applications because racemic forms of peptides can self‐associate more avidly than do single enantiomers. In 1953, Pauling and Corey proposed “rippled β‐sheet” modes of H‐bond‐mediated interstrand assembly for alternating L‐ and D‐peptide strands; this structural hypothesis was complementary to their proposal of “pleated β‐sheet” assembly for L‐peptides. Although no high‐resolution structure has been reported for a rippled β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Our findings have to be put in context with the recent paper by Liu and Gellman, where peptides designed to form two-stranded β-hairpins, composed of half L and half D residues did not exhibit any heterochiral stand pairing detectable by solution NMR. 24 It is noteworthy that one of the systems studied by the authors contained the VFF motif that is present in Aβ and is believed to be important for racemic Aβ fibrillization ( i.e. , Aβ Chiral Inactivation, Aβ-CI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings have to be put in context with the recent paper by Liu and Gellman, where peptides designed to form two-stranded β-hairpins, composed of half L and half D residues did not exhibit any heterochiral stand pairing detectable by solution NMR. 24 It is noteworthy that one of the systems studied by the authors contained the VFF motif that is present in Aβ and is believed to be important for racemic Aβ fibrillization ( i.e. , Aβ Chiral Inactivation, Aβ-CI).…”
Section: Discussionmentioning
confidence: 99%
“… 23 A more recent study by Liu and Gellman is broadly consistent with Chung and Nowick. 24 Our understanding of the interplay of thermodynamics and kinetics that underlie the formation of pleated vs. rippled sheets remains extremely limited. Experiments performed in the laboratories of Schneider, 3,4 Nilsson, 25,26 Raskatov, 7,8 and Torbeev, 27 showed that mirror-image peptide strands may assemble into rippled sheets, but there is also evidence that some sequences may favor homochiral association.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Recently Gellman and co-workers have studied homochiral and heterochiral β-sheet formation in aqueous solution using a β-hairpin model system and have found that peptides containing homochiral peptide strands fold to form β-hairpins, while peptides containing heterochiral peptide strands do not. 19 Intrigued by the conflicting reports of preferred homochiral and heterochiral β-sheet assembly, we set out to reconcile these findings using a minimal aqueous model system that recapitulates both the edge-to-edge hydrogen-bonding interactions that occur in β-sheet formation and additional face-to-face packing interactions that occur in gel and fibril formation. The model system consists of two well characterized β-sheet peptides derived from Aβ 17–23 and Aβ 30–36 , peptides 1a and 1b.…”
Section: Introductionmentioning
confidence: 99%
“…All publication charges for this article have been paid for by the Royal Society of Chemistry rippled b-sheets. 34,35 The development of a rm crystallographic foundation is, therefore, of utmost importance.…”
Section: Introductionmentioning
confidence: 99%